VOLUNTARY DISCLOSURE PROGRAM IN TAXATION AND ITS CERTIFICATES: A PHILOSOPHICAL PERSPECTIVE - Anis Wahyu Hermawan (Journal of Tax Law and Policy, 2022)
The Voluntary Disclosure Program (VDP) for Individual Taxpayers has taken place from 1 January to 30 June 2022. One of the conditions for participating in the second VDP policy is that the Taxpayer revokes the filing of legal remedies (objections, appeals, and so forth), but Law Number 7 of 2021 and Minister of Finance Regulation (PMK) Number 196/PMK.03/2021 does not regulate requests for refunds of overpaid taxes, reduction or elimination of administrative sanctions, reduction or cancellation of incorrect notice of tax assessment, reduction or cancellation of incorrect notice of tax collection, objections, correction, appeal, lawsuit, and/or post-VDP review. It is necessary to carry out a philosophical study related to taxpayers who do not submit legal remedies at the time of submission of the Notification of Asset Disclosure. However, taxpayers will likely file legal remedies related to the 2016-2020 Fiscal Year after receiving a statement. It was concluded that the philosophical applicability of the Certificate of Disclosure of Net Assets had been embodied in legal certainty, a guarantee of justice, and legal effectiveness for taxpayers and the State in the form of completion and certainty of tax rights and obligations for the 2016-2020 tax year.